The role of the State in the Origin and Institutional Evolution of Money in the Light of the Austrian School of Economics - Piaskowski, Otavio Ferrari (2021)
This paper aims to discuss the State’s role in the origin and in the institutional evolution of money in the light of the Austrian School of Economics. This research developed from the context of virtual currencies, which has attracted considerable academic interest in the last few years. Therefore, we employed the theory of the origin of money according to Menger (1985, 2007, 2009), the concept of extended order proposed by Hayek (1948, 1948a, 2017), the theory of market processes as stated by Barbieri (2001), and the theory of institutions developed by Angeli (2007). Considering the context of the virtual currencies and the behavior of the fiat money, it is understood that the State acts as a clog in the process, performed by the market, of the selection of currencies that best carries out their essential functions of medium of exchange, unit of account and storage of value. Similarly, the State harms the process of correction of flaws in the functioning of the financial system.